Time and Cost Performance Improvement by Implementation Top-Down Construction Method (TDC) and 3D Building Information Modeling (BIM 3D) Method in Supertall Building Project - Supriadi Asri, Budi Susetyo (International Journal of Advanced Science and Technology)
Project delay is directly proportional to the impact that occurs, namely, cost overrun. The relationship between time and cost overrun in some developed countries, such as the UK by 10% and the delays were quite large at 67%, or only 33% of the projects that were completed on time. BIM is very effective for several related functions, namely Clash Detection by 56%, Visualization (3D Model) by 42%, and for Scheduling and Site Planning by 12%. This study uses a combination of statistical research and is validated against case studies. The initial stage of statistics used 135 respondents from professionals in the field and analyzed using Relative Importance Index (RII). And in the validation stage of the case study using the method of building information modeling (BIM) with the help of software Tekla Software version 17 and sequential simulation of steel structure installation using the top-down construction method to obtain time and cost-efficiency. The Study Case validation of this research focused on the supertall building construction projects in Central Jakarta. The analysis resulted the factors that influence are Work method (RII=4,489), good planning schedule (RII=4,474), engineering process error (RII=4,459), design revision (RII=4,356) and clash detection (RII=3,978) which is followed up by used BIM Tekla computer application. And the Time performance improvement which is by 21,38% or can be as efficient as 35 working days. Therefore, from originally 162 days can be reduced to only 127 days. And the Cost is Rp 671,614,441. Therefore, the construction cost can be reduced from previously Rp 3,108,615,412 to about Rp 2,437,000,971